PERKEMBANGAN PANGAN LOKAL DI TENGAH INDUSTRIALISASI PANGAN INTERNASIONAL: ANALISIS LITERATURE REVIEW (2020-2025) - Leli Astuni; Eko Handoyo; Indriani Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
International food industrialization has driven significant transformations in global food systems through production modernization, supply chain integration, product standardization, and the expansion of cross-border food trade. This phenomenon has directly affected the existence of local food systems, which have long played a crucial role in food security, cultural identity, and the economic sustainability of local communities. This study aims to analyze the development of local food amid international food industrialization, identify existing research gaps, and formulate future research and policy directions. The study employs a Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was collected from Scopus, Google Scholar, and Crossref databases covering the period from 2020 to 2026. The selection process resulted in 42 articles that met the inclusion criteria and were subsequently analyzed. The findings indicate that international food industrialization exerts both positive and negative impacts on local food systems. Positive impacts include technology transfer, improved production efficiency, market expansion, and product innovation. Conversely, negative impacts involve the homogenization of consumption patterns, the marginalization of small-scale farmers, reduced food diversification, and increased dependence on global food systems. Furthermore, the review reveals that previous studies remain fragmented across the perspectives of food security, food sovereignty, and food industrialization, resulting in the absence of an integrative framework that explains the interrelationship among these dimensions. The novelty of this study lies in its comprehensive synthesis of the dynamics of local food development within the context of international food industrialization through the lenses of food security, food sovereignty, and sustainable food systems.